2018
DOI: 10.3390/molecules23061407
|View full text |Cite
|
Sign up to set email alerts
|

QSAR Study on Antioxidant Tripeptides and the Antioxidant Activity of the Designed Tripeptides in Free Radical Systems

Abstract: In this study, quantitative structure-activity relationship (QSAR) models were determined based on 91 antioxidant tripeptides. We firstly adopted the stepwise regression (SWR) method for selecting key variables without autocorrelation and then utilized multiple linear regression (MLR), support vector machine (SVM), random forest (RF), and partial least square regression (PLS) to develop predictive QSAR models based on the screened variables. The results demonstrated that all the established models have good re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 44 publications
3
69
0
Order By: Relevance
“…Furthermore, they indicated that amino acids having high oxidative susceptibility were those containing nucleophilic sulfur‐containing side chains such as Cys or aromatic side chains such as Trp, Tyr, Phe, and His . Recently, it was also reported using different QSAR models that Trp, Tyr, or Cys at C‐terminus is favorable for antioxidant activity of tripeptides . On the contrary, in previously reported antioxidant peptides, cysteine was found less frequently as one of the constituent amino acids .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, they indicated that amino acids having high oxidative susceptibility were those containing nucleophilic sulfur‐containing side chains such as Cys or aromatic side chains such as Trp, Tyr, Phe, and His . Recently, it was also reported using different QSAR models that Trp, Tyr, or Cys at C‐terminus is favorable for antioxidant activity of tripeptides . On the contrary, in previously reported antioxidant peptides, cysteine was found less frequently as one of the constituent amino acids .…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with the previous findings that most of the important variables that were selected by BOSS originated from the N-terminus or C-terminus ( Figure 2 and Figure 3 B). In addition, studies showed that tripeptides containing Cys (C), Trp (W), and Tyr (Y) residues exhibited strong antioxidant activities [ 8 , 10 ]. Tripeptides YHY and LTC, for the two datasets, respectively, having the highest antioxidant activities is confirmed by our study.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative structure-activity relationship (QSAR), which is a well-recognized tool for estimating chemical activities, has been widely applied for bioactive peptides prediction [ 5 ]. The QSAR models have been successfully built on ACE-inhibitory peptides [ 6 ], antimicrobial peptides [ 7 ], antioxidant peptides [ 8 , 9 , 10 ], antitumor peptides [ 11 ], bitter peptides [ 12 ], and etc. The QSAR study of antioxidant peptides mainly focused on di and tripeptides, because they can be absorbed intact from the intestinal lumen into the bloodstream and then produce biological effects at the tissue level [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…QSAR modeling is one of the most suitable approaches for the prediction and validation of applicable quantitative properties. [ 40 ] Previous studies identified some quinolone derivatives as potent antibiotics. As determined from the technique of model construction, the compounds were divided into a training class (80%) and a test class (about 20%) of quinolones.…”
Section: Methodsmentioning
confidence: 99%